1991
DOI: 10.1162/jocn.1991.3.4.345
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Inhibition of Return in Early Infancy

Abstract: The posterior visual spatial attention system involves a number of separable computations that allow orienting to visual locations. We have studied one of these computations, inhibition of return, in 3-, 4-, 6-, 12-, and 18--month-old infants and adults. Our results indicate that this computation develops rapidly between 3 and 6 months, in conjunction with the ability to program eye movements to specific locations. These findings demonstrate that an attention computation involving the mid-brain eye movement sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
86
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 7 publications
8
86
1
Order By: Relevance
“…A similar finding was reported by Clohessy, Posner, Rothart, and Vecera (1991), who tested infants. In a recent study, Gibson and Egeth (l994a) found evidence for lOR in a temporal order judgment task.…”
supporting
confidence: 89%
“…A similar finding was reported by Clohessy, Posner, Rothart, and Vecera (1991), who tested infants. In a recent study, Gibson and Egeth (l994a) found evidence for lOR in a temporal order judgment task.…”
supporting
confidence: 89%
“…multaneous location cues Posner & Cohen, 1984), age (Clohessy, Posner, Rothbart, & Vecera, 1991), and even personality (Avila, 1995). In addition to these factors, the accuracy of the information provided by a cue has also been reported to influence visual lOR, with the inhibitory component apparently being eliminated when the likelihood that the cue provides accurate spatial information is better than chance (see, e.g., Klein & Taylor, 1994;Rafal et aI., 1989;Rafal & Henik, 1994).…”
mentioning
confidence: 99%
“…Posner and Cohen (1984) originally suggested that the ICE evoked by peripheral cues was the result of sensory stimulation (i.e., an input-based effect). Posner et al (1985), however, found that this ICE had no effect on the perceptual arrival time of targets (see also Klein, Schmidt, & Müller, 1998;Maylor, 1985) but, nevertheless, biased eye movements away (see also Clohessy, Posner, Rothbart, & Vecera, 1991). These findings suggest that the observed ICE may actually represent a motor bias against previously attended locations (i.e., an outputbased effect).…”
mentioning
confidence: 91%